Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Online Akibat Pandemi COVID-19 - Maria Sri Hartati (Keraton: Journal of History Education and Culture, 2021)
COVID-19 is caused by a new type of Corona Virus.  This virus is a new type of virus so the disease is not known until the  COVID-19 outbreak in Wuhan, China in December 2019. Cases of  COVID-19 disease first appeared and infected humans in Wuhan province, China.   The Indonesian government has urged them to stay indoors and isolate themselves. The Government of Indonesia applies PSBB rules which stands for Large-Scale Social Restrictions made in the framework of handling  COVID-19. This is done in the hope that the virus does not spread more widely and healing efforts can run to the maximum. In an effort to limit social restrictions, the Indonesian government has restricted outdoor activities such as educational activities that have been conducted online through online learning. A student who experiences saturation in learning will gain an impropriety in the learning outcomes. Therefore, it is necessary to encourage students to move so that the spirit of learning can have learning achievements. In today's limited conditions, it takes the understanding and creativity of teachers in packaging their online learning in order to attract students' motivation and motivation in following the stages of online learning.